Loop–loop interaction of HIV-1 TAR RNA with N3′ → P5′ deoxyphosphoramidate aptamers inhibits in vitro Tat-mediated transcription - Darfeuille, Fabien (The National Academy of Sciences, 2002)
A hairpin RNA aptamer has been identified by in vitro selection against the transactivation-responsive element (TAR) of HIV-1. A nuclease-resistant N3′ → P5′ phosphoramidate isosequential analog of this aptamer also folds as a hairpin and forms with TAR a loop–loop “kissing” complex with a binding constant in the low nanomolar range as demonstrated by electrophoretic mobility-shift assays and surface plasmon resonance experiments. The key structural determinants, which contribute to the stability of the RNA aptamer–TAR complex, loop complementarity and the GA residues closing the aptamer loop, remain crucial for the N3′ → P5′ aptamer–TAR complex. Moreover, the N3′ → P5′ phosphoramidate aptamer specifically interferes with the binding of a peptide derived from the transactivator protein (Tat) peptide to TAR and selectively inhibits the Tat-mediated transcription in an in vitro assay, which marks this nuclease-resistant aptamer as a relevant candidate for experiments in cells.